Efecto de la enzima transeliminasa sobre la calidad física y sensorial del grano de cacao - López Saavedra, Maira Paola (2022)
Cocoa is one of the crops with the greatest agricultural exploitation due to its great economic importance and is in great demand worldwide. The fermentation process under controlled conditions obtains the enzymes. In the cocoa fermentation process, the development of lactic bacteria is favored, which allows them to hydrolyze the pectins, causing a decrease in the viscosity of the mucilage pulp and favoring the entry of air. The objective of this research is to evaluate the effect of the enzyme transeliminase in the improvement of the physical and sensory quality of cocoa, for which a completely randomized design was used, with nine treatments and three repetitions, with a total of 27 experimental units, the analysis of variance (ADEVA) will be carried out. The effect of transeliminase enzyme dose levels and combinations will be evaluated, resting time, fermentation days and cocoa variety, following the orthogonal design methodology L9 (3)4 de Taguchi. The analysis of the results was carried out in the INFOSTAT program. The application of 60 ml of the transeliminase enzyme in 30 kg of national complex cocoa showed the best physical and sensory characteristics